Revitalizacija potoka Ložnice v Dravinjskih goricah - Vovk Korže, Ana (Geografski vestnik, 2006)
Ložnica is a stream on the eastern part of Dravinske gorice. It is one of river Dravinja's tributaries. Our article deals with the use of sustainable methods to improve biodiversity in Ložnica watershed. Ložnica was regulated in its central part and its water flows along an artificial canal. The system of canal could be modified using the sustainable methods to restore some natural functions of a stream such as water retaining and self-purifying function. Groundwater and biodiversity would benefit from retaining the water in Ložnica valley.
Keywords: Slovenia; Slovenija; tekoče vode; hidrogeografija; Ložnica; regulacija; sonaravni razvoj; revitalizacija; biodiversity; biotska raznovrstnost; ekološko ravnotežje